The A-Z of creative technologies - Connor, AM; Sosa Medina, R (Institute for Computer Sciences, Social Informatics and Telecommunications Engineering (ICST), 2018)
This paper undertakes an initial critical analysis of Creative Technologies as a means to gain insight to the nature of this as an emerging field. The paper utilises an approach previously used in the design discipline to characterise the field through the embodiment of an alphabetised narrative. This is extended through an analysis of the inter-relationships between the identified elements. The outcomes of this work are useful both in terms of identifying outcomes of academic programmes related to Creative Technologies and also stimulating a wider debate around the nature of the field.
Keywords: Creative technologies; Education; Graduate outcomes; Pedagogy